Investigating Hospitality Students’ Level of Anxiety in English Class and Oral Exam Performance - Stefanus Angga Badara Prima (Script Journal: Journal of Linguistics and English Teaching, 2019)
This study reports on a correlation analysis between the level of foreign language anxiety (FLA) of hotel business students and their oral exam performance. The participants of this study were 103 first-year hotel business students of a private university in Jakarta, Indonesia. Using Foreign Language Class Anxiety Scale (FLCAS) questionnaire, it was found that most business students (45%) have medium anxiety. It was also found that fear of negative evaluation is the main source of the anxiety among students. A two-tailed t-test analysis shows no statistical difference between male and female students in 90% of the questionnaire items. A Spearman-rank correlation coefficient analysis shows a significant negative moderate relationship between students’ oral exam performance with FLCAS results